Criminology Study of Sexual Violence in Children - Khairunnisa Taha Oponu; Mutia Cherawaty Thalib; Avelia Mantali (Estudiante Law Journal, 2022)
The purpose of this study is to determine the factors that cause sexual violence that occurs in children and to determine the efforts to overcome cases of sexual violence against children in Gorontalo Regency. The research method used is empirical legal research using a case approach and a conceptual approach. The results of the study found that there were five factors that caused cases of sexual violence against children in Gorontalo Regency, including: the lack of family responsibility, the lack of social control from the community, the technology factor, the alcohol factor, the lack of understanding and the inculcation of norms in the order of life. . The most dominant factors according to the percentage of cases of sexual violence against children in Gorontalo Regency are the lack of parental responsibility and technology (social media) factors. Efforts to prevent and overcome cases of sexual violence against children in Gorontalo Regency are carried out with preventive efforts, namely a form of prevention before the occurrence of cases of sexual violence against children. Preventive efforts are divided into five efforts, including: applying self-awareness, active communication with family, using technology as best as possible, choosing a good environment, socialization from related parties. The other efforts are repressive efforts, one of the forms of efforts to overcome when there have been cases of sexual violence against children. Repressive efforts are carried out by providing criminal sanctions for crimes that have been committed by the perpetrators. As well as repressive efforts to victims by providing psychological assistance and legal assistance.